Auto-Hemoterapia e a invenção da biomedicina: um estudo sociológico sobre controvérsias médicas no Brasil - Costa, Teógenes Luiz Silva da (2013)
This work addresses the controversies within Medicine about health practices considered scientific or not. This research will address the process of health-disease from a social-anthropological perspective. It is considered as empirical cut the prohibition (assigned by the National Health Surveillance Agency- ANVISA) directed at health professionals, the use of therapeutic method called Auto-Hemotherapy (AH), such as technical reclaim legitimacy while legal medical knowledge . Different methodological tools were used, such as: documentary research, interviews, reports on television media (among others). This practice constitutes the use of autologous blood (blood of individual in treatment), punctured the blood stream and applied immediately in the muscle of the practitioner. I try to understand of legitimizing practices that are now considered scientific, sometimes illegitimate. The conclusion of this research concerns to once again, the Social Sciences and Biomedicines debate on new directions for studies about the processes of health-disease.